Analysis Of Ecoprint Results On Cotton Material Using Kenikir Leaves (Cosmos Caudatus) With Mordant Mixture - Diva, Rahmatul; Novrita, I Sri Zulfia (LPPM Institut Seni Indonesia Padangpanjang, 2023)
This research was motivated by the effect of mordant mixture on the results of kenikir leaf ecoprint. The purpose of this study is to describe the direction of color names, clarity of motifs and the effect of mordant mixtures on ecoprint results. This research is experimental descriptive quantitative research conducted by making an ecoprint with steam blanket technique with the combination of 3 mordants. The mordants used were alum, arbor, soda abu, sodium acetate and whiting. The natural motif used was kenikir leaves (cosmos caudatus). The dye used is secang. The type of data in this study is primary data with data collection techniques in the form of questionnaires. The data analysis technique uses frequency percentages and uses the SPSS (Statistical Product And Service Solution) Version 27.0 program. The color name direction of the leaves using a mixture of alum, arbor, and soda abu produces an olive color. A mixture of alum, arbor, and sodium acetate produces a dark brown color. The mixture of alum, arbor, and whiting produces a dark Olive Green color. The results of the motif clarity test with a mixture of alum, arbor, soda abu are categorized as clear, a mixture of alum, arbor, sodium acetate is categorized as clear while a mixture of alum, arbor, and whiting is categorized as unclear.